The Relation of The Ministry of Religion's Interpretation of QS. Al-Ikhlas with The First Principle of Pancasila - Salsabiela; Lukman Nul Hakim; Kamarudin (CV. Doki Course and Training, 2024)
This article aims to explain the relationship between the interpretation of the Ministry of Religious Affairs and Pancasila, especially the first principle. This is motivated by the fact that the Ministry of Religious Affairs has provided signs for religious people to always maintain peace and harmony which includes three things, namely the relationship between followers of the same religion, different religions, and religious leaders with the government. This research uses a type of library research, descriptive analytical, which describes a problem by describing and analyzing the Ministry of Religion's tafsir book. Thus, this article concludes that the first principle in Pancasila, namely “Belief in One God”, contains a strong relationship with the meaning of QS. al-Ikhlash. With this relationship, one can understand the attributes of God that contain the teachings of monotheism so that the first principle of Pancasila can be said to be in accordance with Islam, because Islam upholds the omnipotence of God. The Ministry of Religious Affairs' interpretation of QS. Al-Ikhlas contains an affirmation of the purity of the Godhead and rejects all kinds of polytheism and explains that there is nothing like Him. This also applies to non-Islamic religions that recognize God as One, because the Ministry of Religious Affairs has given freedom to religious people to express their religious practices